Neuromagnetic representation of melodic contour processing in human auditory cortex - Taddeo, Sabrina; Schulz, Martin; Andermann, Martin; Rupp, André (Frontiers in Human Neuroscience, 2022)
The pattern of ups and downs in a sequence with varying pitch can be heard as a melodic contour. Contrary to single pitch, the neural representation of melodic contour information in the auditory cortex is rarely investigated, and it is not clear whether the processing entails a hemispheric asymmetry. The present magnetoencephalography study assessed the neuromagnetic responses of N = 18 normal-hearing adults to four-note sequences with fixed vs. varying pitch that were presented either monaurally or diotically; data were analyzed using minimum-norm reconstructions. The first note of the sequences elicited prominent transient activity in posterior auditory regions (Planum temporale), especially contralateral to the ear of entry. In contrast, the response to the subsequent notes originated from more anterior areas (Planum polare) and was larger for melodic contours than for fixed pitch sequences, independent from the ear of entry and without hemispheric asymmetry. Together, the results point to a gradient in the early cortical processing of melodic contours, both in spatial and functional terms, where posterior auditory activity reflects the onset of a pitch sequence and anterior activity reflects its subsequent notes, including the difference between sequences with fixed pitch and melodic contours.